2020
DOI: 10.7150/thno.48229
|View full text |Cite
|
Sign up to set email alerts
|

P2RX7B is a new theranostic marker for lung adenocarcinoma patients

Abstract: Rationale: The characterization of new theranostic biomarkers is crucial to improving the clinical outcome of patients with advanced lung cancer. Here, we aimed at characterizing the P2RX7 receptor, a positive modulator of the anti-tumor immune response, in patients with lung adenocarcinoma. Methods: The expression of P2RX7 and its splice variants was analyzed by RT-qPCR using areas of tumor and non-tumor lung adenocarcinoma (LUAD) tissues on both immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…Moreover, attempt to facilitate P2RX7 activation in the field of oncology has been limited by the finding that P2RX7 variants expressed by some tumor cells may sustain their proliferation and metabolic activity 2 . To explore this question, we analyzed P2RX7’s functional features in ex vivo lung cancer samples 26 and showed that P2RX7 is functional in leukocytes whereas it is nonfunctional in tumor cells. Considering that P2RX7 is a pro-apoptotic receptor, it makes sense that tumor cells express a nonfunctional receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, attempt to facilitate P2RX7 activation in the field of oncology has been limited by the finding that P2RX7 variants expressed by some tumor cells may sustain their proliferation and metabolic activity 2 . To explore this question, we analyzed P2RX7’s functional features in ex vivo lung cancer samples 26 and showed that P2RX7 is functional in leukocytes whereas it is nonfunctional in tumor cells. Considering that P2RX7 is a pro-apoptotic receptor, it makes sense that tumor cells express a nonfunctional receptor.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, P2X7B exerts a dominant positive activity at the main isoform [ 8 , 37 ]. The P2X7B variant was probably the most studied, as it is the only one to be functional as a small ion channel [ 8 , 18 , 37 , 38 , 39 , 40 , 41 , 42 ]. The P2X7B isoform retains an intron between exons 10 and 11, causing the addition of 18 extra amino acids after residue 346, which is followed by a stop codon [ 18 ] ( Figure 1 ).…”
Section: Human P2x7 Splice Variants and Single-nucleotide Polymorpmentioning
confidence: 99%
“…The P2X7B isoform retains an intron between exons 10 and 11, causing the addition of 18 extra amino acids after residue 346, which is followed by a stop codon [ 18 ] ( Figure 1 ). Nevertheless, P2X7B EC50 is relatively high, and depending upon the cell type and experimental conditions tested, it is not always expressed and functional at the plasma membrane [ 8 , 37 , 41 ]. Another recently identified alternative mRNA for the human P2X7 is P2X7-V3 ( Figure 1 ).…”
Section: Human P2x7 Splice Variants and Single-nucleotide Polymorpmentioning
confidence: 99%
See 2 more Smart Citations